TEACHER SUPERVISION USING TEACHER COMPETENCE ASSESSMENT IN THE ASSESSMENT OF LEARNING IMPLEMENTATION COMPONENTS IN PRIMARY SCHOOL JURUMUDI 5 TANGERANG STATE - Bambang Afriadi; Dahlia Dahlia (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2021)
The focus of this research is mainly based on the elementary school level at SDN Jurumudi 5 Tangerang City hoping that this research topic will enable teachers to expand their knowledge about the impact of classroom climate on their students' learning processes. These factors contribute to a relevant classroom environment in classrooms with students of all ages and grade levels. For students to be able to learn in school, it is not only important for teachers to instruct students on what is in the textbooks, but it is also important that the classroom environment allows students to perform to their highest potential. The focus of this research is related to the classroom environment and its impact on student learning. This study will use an evaluation analysis model with a qualitative and quantitative method approach. Through a qualitative approach, the data collected will try to be processed and presented in a description based on expressions, language, ways of thinking, and the views of the research subject. While the method used in this research is evaluation research. In the analysis of this study using the APKG instrument analysis that has been made by the State University of Jakarta. The data that has been obtained were analyzed using the average of the evaluation results with the following criteria with a range of values ​​1 very not good, 2 enough, 3 good, and 4 very good. The results of the researchers showed results with good criteria, while the components in the assessment that was not optimal could be improved by the teacher. Especially in the use of science and technology, this is due to inadequate school facilities. While the components related to methods, the use of learning resources, and class management are very good. In this case, every ideal teacher class is unique and creative and can be an opportunity to build great classroom conditions and situations between teachers and students